A Planar Wideband Wide-Scan Phased Array Antenna - Wang, Ya-Ru; Zhang, Xiaolin; Jin, Mouping (2021 International Conference on Microwave and Millimeter Wave Technology (ICMMT), 2021)
In this paper, a planar wideband wide-scan phased array antenna (PAA) is designed. The antenna based on tightly coupled dipole elements, is composed of top substrate, middle substrate, bottom substrate, and ground plane. There are circular rings printed periodically on upper surface of top substrate. Between top substrate and middle substrate, it fills with foam. Bow-tie dipoles are printed periodically on upper surface of middle substrate, and de-coupling strips are printed on upper surface of bottom substrate, below the arms of bow-tie dipoles. There are two de-coupling vias at each end of decoupling strips, penetrating the bottom substrate to connect decoupling strips with ground plane. With the working of decoupling strips and de-coupling vias, that used to common-mode suppression and mitigation, the antenna can achieve a 4:1 (from 3 GHz to 12 GHz) bandwidth while scanning up to ±60° in the E-plane and H-plane, subject to VSWR < 3. Its unit has a low profile (0.43λ, λ is the minimum free-space wavelength in the operating band) and size is 0.4λ. The overall structure of the antenna is composed of multi-layers dielectric substrates, which has good reliability and stability.